Metabolically-active bacteria in reclaimed water and ponds revealed using bromodeoxyuridine DNA labeling coupled with 16S rRNA and shotgun sequencing. (1st October 2020) - Malayil, Leena; Ramachandran, Padmini; Chattopadhyay, Suhana; Cagle, Robin; Hittle, Lauren; Ottesen, Andrea; Mongodin, Emmanuel F.; Sapkota, Amy R.
Highlights: Detected metabolically-active bacteria in reclaimed water and ponds using coupled method. Actinobacterium spp ., Flavobacterium spp., and Aeromonas spp . dominated the waters. Antibiotic resistance and virulence genes more frequently observed in non-labeled samples. Abstract: Understanding the complex microbiota of agricultural irrigation water is vital to multiple sectors of sustainable agriculture and public health. To date, microbiome characterization methods have provided comprehensive profiles of aquatic microbiotas, but have not described which taxa are likely metabolically-active. Here, we combined 5‑bromo‑2′-deoxyuridine (BrdU) labeling with 16S rRNA and shotgun sequencing to identify metabolically-active bacteria in reclaimed and agricultural pond water samples ( n  = 28) recovered from the Mid-Atlantic United States between March 2017 and January 2018. BrdU-treated samples were significantly less diverse (alpha diversity) compared to non-BrdU-treated samples. The most abundant taxa in the metabolically-active fraction of water samples (BrdU-treated samples) were unclassified Actinobacteria, Flavobacterium spp ., Pseudomonas spp. and Aeromonas spp . Interestingly, we also observed that antimicrobial resistance and virulence gene profiles seemed to be more diverse and more abundant in non-BrdU-treated water samples compared to BrdU-treated samples. These findings raise the possibility that these genes may be associated more with relic (inactive) DNA present in the tested water types rather than viable, metabolically-active microorganisms. Our study demonstrates that the coupled use of BrdU labeling and sequencing can enhance understanding of the metabolically-active fraction of bacterial communities in alternative irrigation water sources. Agricultural pond and reclaimed waters are vital to the future of sustainable agriculture, and thus, the full understanding of the pathogenic potential of these waters is important to guide mitigation strategies that ensure appropriate water quality for intended purposes. Graphical abstract: Image, graphical abstract